PROFIL KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII MTs PADA MATERI LINGKARAN - Nida Nafi; Ibrahim Ibrahim (STKIP Andi Matappa, 2021)
Low problem solving ability will give students a problem. These problems are part of the background of this research. The purpose in this study was to give description about the problem-solving profile in class VIII students on circle material which is based on the differences in mathematical abilities in terms of the Polya stage. Four (4) grade VIII students of MTs N 3 Banjarnegara were the chosen targeted subjects in this research, each of which consisted of students with different categories which are high and medium to low cabilities. The instrument in this study was the researcher, who received assistance using interviews and also some questions on a test for solving a problem in the field of mathematics. The results in this study showed that students who have high abilities able to carry out the calculation steps, but students who had high abilities were more dominant in being able to understand the problem. Students with moderate abilities are more dominant in being able to carry out calculations in the step of planning completion. Meanwhile, low-ability students are able to perform calculation steps, but low-ability students experience a little difficulty in carrying out each of the steps.